PENGENDALIAN PENCEMAR DAN KERUSAKAN SITU UNTUK MENJAGA DAYA TAMPUNG BEBAN PENCEMAR PADA SITU GEDE KOTA BOGOR - Yannuariza Lazuardini, Muthia; Hendrawan, Diana; Megagupita Putri Marendra, Sheilla (JURNAL PENELITIAN DAN KARYA ILMIAH LEMBAGA PENELITIAN UNIVERSITAS TRISAKTI, 2025)
Situ Gede is one of the natural shallow lake in Bogor City with an area of 7.9 hectares. Increasing population activities directly or indirectly will have an impact on water quality, capacity and sustainability of the ecosistem. This study aims to identify the source of pollution, analyze the status of water quality and evaluate its capacity. Identification of activities was carried out by surveying the catchment area of Situ Gede and looking at the direction of water flow. Water quality status is calculated using the Pollutant Index (IP). The Pollutan Load Capacity is calculated by referring to the Minister of Environment Regulation No. 28 of 2009. The results of this study are that the main source of pollutants from settlements, the water quality status is 3.80 (lightly polluted). The Carrying Capacity of the Pollutant Load (DTBP) of BOD is 68.31 kg/year, the existing BOD load is 114.62 kg/year. DTBP COD is 569.29 kg/year, existing COD load is 984.65 kg/year and DTBP phosphate is 0.68 kg/year, existing phosphate load is 19.36 kg/year. Pollution control is carried out by making communal WWTP, dredging sediment periodically, retaining incoming garbage and maintaining the boundary as a green open space. The implication of this study is the maintenance of water quality and the capacity of pollutant loads for the sustainability of the ecosystem